2016
DOI: 10.1016/j.jnucmat.2016.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of oxygen thermo-migration in PWR UO2 fuels during power ramps using in-situ oxido-reduction indicators

Abstract: The present study describes the in-situ electrochemical modifications which affect irradiated PWR UO 2 fuels in the course of a power ramp, by means of in-situ oxido-reduction indicators such as chromium or neo-formed chemical phases. It is shown that sub-stoichiometric irradiated fuels under temperature gradient such as that occurring during high power transients are submitted to strong oxido-reduction perturbations, owing to radial migration of oxygen from the hot center to the cold periphery of the pellet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…As a consequence the O/M ratio increases during the life of the fuel material under neutronic flux. Studies carried out by Riglet-Martial et al [32] showed that thermal gradient characterizing the fuel material during irradiation is the source of a strong reduction-oxidation reaction leading to migration of the oxygen from the center of fuel pellet to its periphery which induces a decrease of O/M ratio in the central zone. It has been showed by an expert group and then reported by the French Autority of Nuclear Safety [33] that in a hypothetical accidental case leading to fuel melting, this shall appear in the central region of the PWR fuel pellet and progressively evolve towards the periphery.…”
Section: Effect Of Oxygen To Actinides Ratiomentioning
confidence: 99%
“…As a consequence the O/M ratio increases during the life of the fuel material under neutronic flux. Studies carried out by Riglet-Martial et al [32] showed that thermal gradient characterizing the fuel material during irradiation is the source of a strong reduction-oxidation reaction leading to migration of the oxygen from the center of fuel pellet to its periphery which induces a decrease of O/M ratio in the central zone. It has been showed by an expert group and then reported by the French Autority of Nuclear Safety [33] that in a hypothetical accidental case leading to fuel melting, this shall appear in the central region of the PWR fuel pellet and progressively evolve towards the periphery.…”
Section: Effect Of Oxygen To Actinides Ratiomentioning
confidence: 99%
“…In this work, to by-pass these difficulties, we have identified the heat of transport and thermodynamic factor by inverse analysis using the weight fractions of chromium measured by EPMA along the pellet radius after several power ramps [8]. Figure 7 illustrate the measured evolution of chromium content at the center of a fuel pellet during the 12h long holding period of a power ramp (maximum power 470 W/cm).…”
Section: Oxygen Transport Parameters For Irradiated Fuelmentioning
confidence: 99%
“…In a recent paper on power ramped Cr-doped fuels [8], it was shown that the oxygen potential along the fuel radius decreases significantly during the high power period of a power ramp. These results were attributed to oxygen thermodiffusion (diffusion of oxygen from the hot pellet center to the cold pellet periphery), a phenomenon observed not only in Sodium Fast Reactor (SFR) fuels due to the high temperature gradients at hand in these fuels [9,10], but also in BWR power ramped fuel pellets as reported by Adamson et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Kim [7] [20]. Deviasi nilai stoikiometri UO 2 sangat mempengaruhi kinerja pelet UO 2 di reaktor [20][21]. Pelet UO 2 yang hiperstoikiometri bersifat lebih plastis sehingga mempunyai laju mulur semakin meningkat dengan semakin besar nilai deviasi stoikiometri.…”
Section: Pendahuluanunclassified
“…Pada temperatur tinggi, peningkatan laju mulur dan laju difusi dapat mengakibatkan terjadinya swelling pada pelet UO 2 yang mendegradasi kemampuan retensi produk fisi dan menurunkan integritas kelongsong karena terjadi PCI (pelletcladding interaction). Bila dikaitkan dengan pustaka diatas [20,21] …”
Section: Pendahuluanunclassified